Influence of stubble quality and degree of soil-stubble contact on N2O emission - COSENTINO, Vanina Rosa Noemí; MINERVINI, Mariana G.; TABOADA, Miguel A. (Plant, soil and environment, 2017)
The organic residue position and C/N ratio regulate decomposition rate and, therefore, nitrogen (N) release to the soil. The N2O emission from soil is produced by nitrification and denitrification processes. These processes are affected by the mineral N concentration, water filled pore space (WFPS) and soil temperature. The N2O emission from soils covered by corn and soybean residues has been little studied so far. The aim of the present study was to evaluate the C/N ratio of corn and soybean residues and their contact degree with the soil on soil N2O emissions. A greenhouse experiment was conducted with a completely randomized design and N2O emission was determined using closed chambers. The N2O emissions were affected by the residue position and not by its origin (soybean = corn). Treatments with residue on the surface had the highest N2O emissions at the beginning of the trial, while residue incorporation showed constant values of N2O emission during the experiment. Soil N2O emissions were explained by two controlling variables: the WFPS and the N-NO3– soil concentration. The WFPS separated the emission values of N2O into two groups (threshold value near 77% WFPS). When the WFPS exceeded the threshold value, the emissions of N2O were partially explained by the concentration of N-NO3– soil.